MAIN CHARACTER'S PERSONALITY IN JEANNETTE WALLS’ THE GLASS CASTLE - Gowasa, Stefanus Septiaman; Silitonga, Andi Jaihutan (LPPM Universitas Darma Agung, 2024)
This thesis dealth with main characters personality In Jeannette Walls’ The Glass Castle. The analysis of this thesis focused on main character’s personality of Jeannette. The problem of the study in this thesis are What are types of personality, What is the most dominan type, and the impacts of the main character’s most dominat personality in Jeannette Walls’ The Glass Castle, according to Goldberg Lewis’ theory. While completing this thesis, the writer Apply library research descriptive qualitative methods in order to again the appropriate results as the writer hope to. The result of this study are: (1)The types personality used by the main character in Jeannette Walls’ The Glass Castle are: Openness, Conscientiousness, Extraversion, Agreeableness and Neuroticsm. (2)The most dominant type of personality used by the main character in Jeannette Walls’ The Glass Castle is Conscientiousness. (3) The impact of dominantly personality are: (a) Bullied make mentally stronger; She was frequently bullied by other children because they lived in the garbage. This made her try to escape poverty and become more ambitious. (b) Personality Changing Causes of Permissive parenting; Parents failing to provide food, clothing, shelter, and most importantly, love and attention to a child can harm their physical, mental or emotional condition. This results in children having low self-esteem and having difficulty surviving.